Breaking the Cycle of Violent Crime and Punishment: The Promise of Neuronormalization. Issue 1 (18th December 2020) - Denson, Thomas F.
Abstract: Violent crime elicits demand for punishment from the public, which can influence policy toward offenders. Paradoxically, harsh punishments such as incarceration often increase offending rather than deter it, which produces a cycle of violent crime and punishment. Violent offenders frequently possess risk factors that influence brain structure and function. These risk factors are genetic predisposition toward violence, adverse childhood experiences, alcohol use, and traumatic brain injury. The alteration in brain structure and function appears primarily in networks involved in threat detection (e.g., biased sensitivity to provocation), self‐regulation (e.g., control over anger and aggressive urges), and social cognition (e.g., thinking about others' motives). If there is no treatment in people with these risk factors, brain responses to anger provocation will likely increase risk for reactive aggression. As a method to circumvent the cycle of violence and punishment, this review discusses the notion of normalizing brain responses to provocation such that they resemble responses of nonviolent people. A growing body of research suggests that brain normalization can occur by using biomedical instruments such as pharmaceuticals and brain stimulation to enhance moral behavior. Normalizing brain function via moral bioenhancement should inhibit reactive aggression. If such normalization occurs, there is no violent act to punish and hence the cycle of crime and punishment is broken. Policy makers may consider investing in trials of moral bioenhancement that could support existing treatments to reduce violence and recidivism and their associated costs.